The Influence of Brand Preference and Product Quality on Consumer Loyalty - Nurlia, N.; Martini, Andi Indra; Naim, Muh. Rezky (Manunggal Halim Jaya, 2025)
The objectives of this study are: 1. To determine the effect of brand preference and product quality on consumer loyalty of Beat Street motorcycles at Astra Honda Motor, Mamuju Regency. 2. To determine the effect of brand preference and product quality simultaneously on consumer loyalty of Beat Street motorcycles at Astra Honda Motor, Mamuju Regency. This quantitative study has two independent variables and one dependent variable. The test tools used are 1) validity test, 2) reliability test, 3) multiple linear regression test, t-test (partial), and f-test (simultaneous). The sample used in this study was 96 respondents.. The research data processing used multiple linear regression with SPSS software version 24.0 to partially read the direction of independent variables' influence on the dependent variable using t-test and F-test. The results of the study showed that brand preference has a partially significant influence on consumer loyalty of Beat Street motorcycles at Astra Honda Motor, Mamuju Regency. Product quality partially influences consumer loyalty to Beat Street motorcycles at Astra Honda Motor, Mamuju Regency. The results also showed that brand preference and product quality significantly influence consumer loyalty to Beat Street motorcycles at Astra Honda Motor, Mamuju Regency.